Toksisitas Letal (LC50) Zat Surfaktan Linear Alkylbenzene Sulfonate terhadap Ikan Cere (Gambusia affinis): Lethal Toxicity (LC50) of Linear Surfactant Alkylbenzene Sulfonate on Mosquito Fish (Gambusia affinis) - Iffi Rizkiya; Yuniarti Dwi Astuti; Nabila Dhiya Ulhaq; Kania Dewi Rafa; Dela Putri Amalia; Dyah Perwitasari (Departemen Biologi, Institut Pertanian Bogor, 2023)
Mosquito fish (Gambusia affinis) is a species often used as a bioindicator because it has high adaptability to water quality changes. Linear alkylbenzene sulfonate (LAS) is a surfactant often found in waters and can cause death for the biota that lives in it. This study aimed to analyze the impact of LAS surfactant on the survival of mosquito fish and to determine the minimum concentration of LAS surfactant that can cause death and tissue damage. Research conducted during April 2022 using 500 mosquito fishes. We did several tests, including a lethal toxicity test to find out the concentration of LAS surfactant that can cause death and tissue damage. The results showed that the LC50 values of LAS surfactants at exposure times of 24, 48, 72, and 96 hours were 7.64, 7.43, 7.29, and 6.83 mg/L, respectively. Mosquito fish blood glucose levels at LAS concentrations of 0, 2.65, 4.30, 6.97, and 11.3 were 56, 75, 79.6, 95, and 95.6 mg/dl. Exposure to LAS surfactant in mosquito fish can cause gill damage in the form of edema, lamella fusion, hyperplasia, lamellae epithelium swelling, and gill filaments necrosis. Another damage occurs to the liver in the form of blockage of blood vessels and sinusoids, hyperplasia, widening of the hepatic sinusoid gap, fat accumulation, and necrosis of hepatocytes.